Cancer Nanotheranostics - Gopinath, P.; Uday Kumar, S.; Matai, Ishita; Bhushan, Bharat; Malwal, Deepika; Sachdev, Abhay; Dubey, Poornima; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2015)
This Brief provides a clear insight of the recent advances in the field of cancer theranostics with special emphasis upon nano scale carrier molecules (polymeric, protein and lipid based) and imaging agents (organic and inorganic).
Preface -- Acknowledgements -- Cancer Nanotheranostics.
Keywords: Engineering; Molecular biology; Medical biochemistry; Medical physics; Radiation; Nanotechnology; Biomedical engineering; Biomaterials; Engineering; Biomedical Engineering; Molecular Medicine; Biomaterials; Medical Biochemistry; Medical and Radiation Physics; Nanotechnology and Microengineering; Electronic books